Writing Plague - Thomas, Alfred. author. aut Link
XXIV, 265 p. 32 illus., 30 illus. in color.
Keywords: Writing Plague: Language and Violence from the Black Death to COVID-19 brings a holistic and comparative perspective to “plague writing” from the later Middle Ages to the twenty-first century. It argues that while the human “hardware” has changed enormously between the medieval past and the present the human “software” has remained remarkably similar across time. Through close readings of works by medieval writers like Guillaume de Machaut, Giovanni Boccaccio, and Geoffrey Chaucer in the fourteenth century, select plays by Shakespeare, and modern “plague” fiction and film, Alfred Thomas convincingly demonstrates psychological continuities between the Black Death and COVID-19. Thomas highlights the danger of scapegoating vulnerable minority groups such as Asian Americans and Jews in today’s America. This wide-ranging study will thus be of interest not only to medievalists but also to students of modernity as well as the general reader.